Shared musical creativity: teaching composer-performer collaboration - Cardassi, Luciane; Bertissolo, Guilherme (Revista Vórtex, 2020)
This paper focuses on teaching composer- performer collaboration as a path to new paradigms of 21st century art-making. First, we discuss the interplay between theory and practice in creative musical processes, with special attention to the performative modality of composition. Then, we approach collaboration itself, considering how the term has been both overused and misunderstood for decades. Finally, we present a case study of teaching composer- performer collaboration at the graduate level, in the "Atelier for Composition and Performance" (AtelieÌ‚ de ComposicÌ§aÌƒo e Performance ContemporaÌ‚nea), at the Federal University of Bahia.